Perbandingan Aktivitas Belajar Pai Antara Siswa Yang Berlatar Belakang Pendidikan MTSN Dengan Siswa SMPN - Tiara Indah Lestari; Darul Ilmi; Jasmienti Jasmienti; Alimir Alimir (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
The purpose of this research is to be able to see how the comparison of their activeness in carrying out the teaching and learning process. This research uses the type of field research (field research) with the type of comparative quantitative research. Data collection techniques using a questionnaire distributed to several respondents. Furthermore, the data analysis technique performs steps such as finding the mains of each variable, looking for the standard deviation of each variable, and also looking for the t test. The results showed that the average PAI learning activity of students with an MTsN educational background was 93.09 with a percentage of 93% and students with a junior high school background of 94.09 with a percentage of 94% with a difference or comparison of a percentage of 1.09%. students with a junior high school background are more active than students with an MTs background, this is evidenced by the t test obtained by 1.65, which is greater than the t table with a significant level of 5% with a magnitude of 0.288 or 1.65 > 0.288 this result also shows that students with a junior high school background are more active than students with an MTs background.